Parent-reported health care expenditures associated with autism spectrum disorders in Heilongjiang province, China - Wang Jia; Zhou Xue; Xia Wei; Sun Cai-Hong; Wu Li-Jie; Wang Jian-Li; Tomoda Akemi (BMC, 2012)
Abstract Background The aim of this study was to determine the health expenses incurred by families with children with autism spectrum disorder (ASD) and those expenses' relation to total household income and expenditures. Methods In this cross-sectional study, health care expenditure data were collected through face-to-face interviews. Expenses included annual costs for clinic visits, medication, behavioral therapy, transportation, and accommodations. Health care costs as a percentage of total household income and expenditures were also determined. The participants included 290 families with ASD children who were treated at the Children Development and Behavior Research Center, Harbin Medical University, China. Results Families with ASD children from urban and rural areas had higher per-capita household expenditures by 60.8% and 74.7%, respectively, compared with provincial statistics for 2007. Behavioral therapy accounted for the largest proportion of health expenses (54.3%) for ASD children. In 19.9% of urban and 38.2% of rural families, health care costs exceeded the total annual household income. Most families (89.3% of urban families; 88.1% of rural families) in that province reported higher health care expenditures than the provincial household average. Conclusion For families with ASD children, the economic burden of health care is substantially higher than the provincial average.